Using Films to Teach Listening Comprehension - Eka Rizki Amalia; Nurulazizah Ria Kusrini; Pungky Ramadhani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
ABSTRACTUsing films for classroom activities is often doubted as an appropriate and meaningful way to teach listening comprehension. Since the film is authentic material and far from pedagogical instruction, its use has rarely been paid attention to. This paper aims to prove that using film can be an alternative and effective way to teach listening comprehension. The problems which are commonly faced by the students in film viewing for listening activities and the proposed techniques along with film viewing activities are discussed further in this paper. The result of the discussion shows that using film to teach listening comprehension is motivating, enhancing and appealing for the students.ABSTRAKMenggunakan film untuk kegiatan di kelas sering diragukan sebagai cara yang berarti dan sesuai untuk mengajarkan listening comprehension. Karena film adalah materi otentik dan dianggap jauh dari konten pedagogik, penggunaan film jarang sekali diberi perhatian. Artikel ini bertujuan untuk membuktikan bahwa menggunakan film untuk kegiatan pembelajaran dapat menjadi salah satu alternatif dan cara yang efektif untuk mengajarkan listening comprehension. Artikel ini membahas masalah-masalah yang umum dihadapi oleh siswa dalam kegiatan pemutaran film, teknik-teknik untuk memutar film, dan kegiatan-kegiatan dalam pemutaran film untuk kegiatan listening di kelas. Hasil pembahasan menunjukkan bahwa menggunakan film untuk mengajarkan listening comprehension sangat memotivasi, menggugah dan menarik bagi siswa. How to Cite: Amalia, E.R., Kusrini, N. R., Ramadhani, P.(2019). Using Films to Teach Listening Comprehension . IJEE (Indonesian Journal of English Education), 6(2), 119-132. doi:10.15408/ijee.v6i2.14531